Applying the Delphi Technique in Developing the Employability Scale for Engineering Technology Graduates (Journal of Contemporary Educational Policies and Practices, 2025)
The employability scale is crucial in implementing graduates’ employability measurement. The research group’s previous study proposed applying the Delphi method to develop the employability scale for engineering technology graduates. This paper reports on exploiting the Delphi method in practice. The employability scale was proposed to cover 51 items in four constructs of technical knowledge, technical skills, generic skills, attitude and other attributes. The Delphi process involves 20 experts from industry employers and university lecturers in the two rounds to adjust the employability scale. In the first round, expert assessments were collected by using a three-point Likert scale. In the next round, the same experts were invited for a group interview to revise the first-round reports and concur on the modifying constructs and items. The expert responses were analysed by descriptive statistical techniques. After two rounds of expert feedback with the addition of 3 items, deletion of 2 items and adjustment of 23 items, the employability scale was updated to consist of four constructs with 52 items. It is recommended that further studies should validate this employability scale and measure the employability of graduates from a Vietnamese university.
Keywords: Engineering technology; employability; Delphi technique; group discussions